Interleukin-17 in Chronic Inflammatory Neurological Diseases - Milovanovic, Jelena; Arsenijevic, Aleksandar; Stojanovic, Bojana; Kanjevac, Tatjana; Arsenijevic, Dragana; Radosavljevic, Gordana; Milovanovic, Marija; Arsenijevic, Nebojsa (Frontiers in Immunology, 2020)
Critical role of IL-17, cytokine produced by T helper 17 (Th17) cells, has been indicated in the pathogenesis of chronic inflammatory and autoimmune diseases. Positive effects of blockade of IL-17, secreted by autoreactive T cells, has been shown in various inflammatory diseases. Several cytokines, whoose production is affected by environmental factors, control Th17 differentiation and their maintenance in tissues during chronic inflammation. In this review we discuss the roles of IL-17 in the pathogenesis of chronic neuroinflammatory conditions, experimental autoimmune encephalomyelitis (EAE) and Alzheimer's disease. The role of environmental stimuli in Th17 differentiation is also summarized with highlighted role of viral infection in the regulation of pathogenic T helper cells in EAE.